Attitudes Toward Assisted Suicide and Life-Prolonging Measures in Swiss ALS Patients and Their Caregivers - Stutzki, Ralf; Schneider, Ursula; Reiter-Theil, Stella; Weber, Markus (Frontiers in Psychology, 2012)
Objectives: In Switzerland, assisted suicide (AS) is legal, provided that the person seeking assistance has decisional capacity and the person assisting is not motivated by reasons of self-interest. However, in this particular setting nothing is known about patients’ and their caregivers’ attitudes towards AS and life-prolonging measures. Methods: Data was retrieved through validated questionnaires and personal interviews in 33 patients and their caregivers covering the following domains: physical function according to the revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS-R), demographic data, quality of life (QoL), anxiety, depression, social situation, spirituality, burden of disease, life-prolonging and life-shortening acts. Results: In patients the median time after diagnosis was 9 months (2-90) and the median ALS FRS-R score was 37 (22-48). The majority of patients (94%; n=31) had no desire to hasten death. Patients’ and caregivers’ attitudes towards Percutaneous Endoscopic Gastrostomy (PEG) and Non-Invasive Ventilation (NIV) differed. Significantly more patients than caregivers (21.2% versus 3.1%) stated that they were against NIV (p=0.049) and against PEG (27.3% versus 3.1%; p=0.031). Answers regarding tracheotomy were not significantly different (p= 0.139). Caregivers scored significantly higher levels of “suffering” (p=0.007), “loneliness” (p=0.006) and “emotional distress” answering the questionnaires (p<0.001). Suffering (p<0.026) and loneliness (p<0.016) were related to the score of the Hospital Anxiety and Depression Scale (HADS) in patients. Conclusion: A liberal legal setting does not necessarily promote the wish for AS. However, the desire to discuss assisted suicide is prevalent in ALS patients. There is a higher level of suffering and loneliness on the caregivers’ side. A longitudinal study is warranted.